HIV Testing Among Muslim Women in the United States: Results of a National Sample Study (Health Equity, 2021)
Purpose: More than one million Americans are living with human immunodeficiency virus (HIV), and less than half of Americans have ever accepted an HIV test. There are no national HIV testing estimates for Muslim Americans, an underserved and often stigmatized population. Considering the lack of HIV testing estimates for this population, we conducted an exploratory study on HIV testing and potential associates in American Muslim women from across the United States. Methods: We applied logistic regression models to examine the Muslim Women's Health Project data, collected in 2015 (N=218). Results: Health care engagement and intimate partner violence were significantly associated with having been tested for HIV. Respondents using contraceptives received an influenza vaccination, and received an abnormal pap test had more than two times higher odds of having been tested for HIV (odds ratio [OR]=2.56, OR=2.43, OR=2.93, respectively; p<0.05 all). Having been sexually abused was associated with more than two times higher odds of having been tested for HIV (OR=2.49; p<0.05). Conclusion: Respondents reported higher rates of HIV testing as compared with the general public, signaling HIV knowledge, engagement in preventative health care, and possibly HIV risk. Scholars and practitioners should not assume that Muslim patients are at low risk for HIV and do not engage in HIV-risk behaviors. Thus, assumptions about Muslims women's willingness to accept HIV testing should be further examined to elucidate HIV risk among this population.